2022
DOI: 10.1007/s10533-022-00964-2
|View full text |Cite
|
Sign up to set email alerts
|

Determining patterns in the composition of dissolved organic matter in fresh waters according to land use and management

Abstract: In fresh waters, the origins of dissolved organic matter (DOM) have been found to exert a fundamental control on its reactivity, and ultimately, its ecosystem functional role. A detailed understanding of landscape scale factors that control the export of DOM to aquatic ecosystems is, therefore, pivotal if the effects of DOM flux to fresh waters are to be fully understood. In this study we present data from a national sampling campaign across the United Kingdom in which we explore the variability in DOM composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 82 publications
(125 reference statements)
0
1
0
Order By: Relevance
“…We then move on to a suite of papers in which the authors apply these techniques at scale, often over multiple catchments with varying environmental character, to reveal the origins of DOM in freshwaters as this varies in space in time. The multi-catchment research of Williamson et al (2021) 2021) tackles a major river basin, the Mississippi, USA, using optical and molecular-scale approaches to reveal the impacts of anthropogenic land cover on DOC flux and the molecular composition of the stream DOM pool, with many parallels to be drawn between this study and the DOC findings reported by Yates et al (2022) and Williamson et al (2021). Voss et al (2022) then use a suite of molecular and isotope chemistry approaches to infer the likely sources of DOC and the role of organic matter respiration on stream DOM pool composition in another large river basin: the Fraser River, in SW Canada.…”
Section: Exploring New Dimensions In the Diagnosis Of Ecosystem Respo...mentioning
confidence: 96%
“…We then move on to a suite of papers in which the authors apply these techniques at scale, often over multiple catchments with varying environmental character, to reveal the origins of DOM in freshwaters as this varies in space in time. The multi-catchment research of Williamson et al (2021) 2021) tackles a major river basin, the Mississippi, USA, using optical and molecular-scale approaches to reveal the impacts of anthropogenic land cover on DOC flux and the molecular composition of the stream DOM pool, with many parallels to be drawn between this study and the DOC findings reported by Yates et al (2022) and Williamson et al (2021). Voss et al (2022) then use a suite of molecular and isotope chemistry approaches to infer the likely sources of DOC and the role of organic matter respiration on stream DOM pool composition in another large river basin: the Fraser River, in SW Canada.…”
Section: Exploring New Dimensions In the Diagnosis Of Ecosystem Respo...mentioning
confidence: 96%
“…Additionally, it has been reported that in deforested sites, there is an increase in the relative contents of recalcitrant compounds (e.g., condensed hydrocarbons, lignin, and tannins) [ 10 ]. Meanwhile, deforestation can also affect the composition of DOM by altering soil microbial activities responsible for its decomposition [ 11 ]. However, the relationship between the chemodiversity of DOM and deforestation in the Amazon basin, as well as the underlying mechanisms that control the diversity of labile and recalcitrant compounds in tropical soils, is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%